2019
DOI: 10.1186/s12954-019-0282-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV- and AIDS-related knowledge and attitude of residents in border regions of Vietnam

Abstract: BackgroundResidents in border areas are vulnerable to HIV/AIDS due to high rates of risk behaviors such as unprotected sexual practices or illicit drug use. Improving knowledge and attitude toward HIV/AIDS prevention and treatment are vital to diminish the burden of the HIV epidemic in this setting. However, evidence about this issue in Vietnam has been limited. This study aims to explore the knowledge and attitude toward HIV/AIDS among people in Vietnam border zones.MethodsWe conducted a cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…The odds of having comprehensive HIV-knowledge instead of having low to moderate for married youths compared to never-married were lower by about 21%, controlling for the effect of the other predictors in the model. In a study conducted among university students in UAE, marital status didn't make a difference on level HIV-knowledge [42] but the current finding agrees with the study conducted in Vietnam in that those who live with their spouses were more likely to have knowledge of HIV than singles [51]. This probably is because of the different age groups included in either of the studies and also it could be due to cultural and norm differences across the countries in which the studies were conducted.…”
Section: Discussionsupporting
confidence: 85%
“…The odds of having comprehensive HIV-knowledge instead of having low to moderate for married youths compared to never-married were lower by about 21%, controlling for the effect of the other predictors in the model. In a study conducted among university students in UAE, marital status didn't make a difference on level HIV-knowledge [42] but the current finding agrees with the study conducted in Vietnam in that those who live with their spouses were more likely to have knowledge of HIV than singles [51]. This probably is because of the different age groups included in either of the studies and also it could be due to cultural and norm differences across the countries in which the studies were conducted.…”
Section: Discussionsupporting
confidence: 85%
“…However, consistent with the previous studies (Yang et al, 2017; Yang et al, 2018), our results showed that most Yi family caregivers with a lower education level, most of them were illiterate. Limited educational levels could have led to a lack of HIV knowledge (Hoang et al, 2019), and caregivers could have relied on care experience that was accumulated gradually during the process of caring for PLWH. However, HIV knowledge acquired this way is not scientific or systematic and could have led to an inability to respond to and deal with new difficulties in a timely and safe manner when the illness changed.…”
Section: Discussionmentioning
confidence: 99%
“…During the survey, we found that employed women held a high-level discriminatory attitude than those who were unemployed. A study from Vietnam indicated that the participants' occupation was significantly associated with attitudes towards PLHIV (Hoang et al, 2019). Employed respondents reported that they experienced a low level of stigma and discrimination compared to those unemployed in Ghana (Tenkorang & Owusu, 2013).…”
Section: Employment and Discriminatory Attitudesmentioning
confidence: 99%
“…We found that women with high exposure to mass media were less likely to possess a discriminatory attitude towards PLHIV. Hoang et al (2019) indicated that sources of information about HIV/AIDS were significantly associated with knowledge and attitudes towards PLHIV. The respondents exposed to mass media were almost 5 to 16 times more likely to be aware of knowledge transmission and prevention and HIV/AIDS-related services.…”
Section: Media Exposure and Discriminatory Attitudesmentioning
confidence: 99%